Female Teachers at Grammar and Teacher Training Schools sanctioned in Andalusia during the Spanish Civil War: biographical notes - Grana Gil, Isabel; Martín Zúñiga, Francisco; Trigueros Gordillo, Guadalupe (Historia y Memoria de la Educación, 2022)
The objective of the article is to “rescue from oblivion” and, therefore, “make visible”, the female teachers at the grammar and teacher training schools of Andalusia that were sanctioned during the Spanish civil war. Silence leads to oblivion on the part of the protagonists themselves and, above all, to the ignorance of those who have not lived the facts. We intend to rescue these teachers from that oblivion and thereby recover their name and their memory. Here we have applied the historical-educational methodology, based on a review of the existing literature and, fundamentally, the use of primary sources. We have consulted the publications on the development of the different purging processes and gone to the primary sources—personal purging files, minutes of the teacher training schools, etc.— to make a portrait, however brief, of the different teachers. We also resorted to the scarce historiography that we found. The work is structured in three parts: a first part is dedicated to reflecting on the peculiarities of internal exile to which the teachers were subjected; in a second moment we highlight the general peculiarities of the purges, both at the level of secondary schools and teacher-training schools, in terms of the number of teachers sanctioned, charges pressed, type of sanctions, etc.; and finally, we focus on the biographies of the teachers.